Ibsen’s The Pillars of Society: Female Protest against Patriarchy - Bhatta, Arjun Dev (NUTA Journal, 2020)
This study explores social relationship between male and female in Henrik Ibsen’s play “The Pillars of Society”. The first part of the study analyzes a sexist society in which male characters subjugate females through their hegemonic power. The female characters appear meek, submissive and voiceless. The second part of this study examines the revolutionary role of the female characters who raise their voice against all-pervasive patriarchal power. They protest against male formulated institutions which have kept women voiceless and marginalized. Being dissatisfied with the defenders of patriarchal status quo, Ibsen’s female protagonists come to the fore to challenge prevailing social conviction about femininity and domesticity. They lead a crusade to establish their position and identity as human beings equal to men. In this play, the female characters Lona, Martha and Dina hold a revolutionary banner to protest against male domination of female. In their constant struggle, they win while the male characters become loser. This study analyses the voice of these leading female characters in the light of feminist theory proposed by scholars such as Kete Millett and Sylvia Walby.